Enhancing Employee Engagement by Transformational Leadership and Empowerment with Job Satisfaction as Mediator - Indah Rizki Maulia (Dinasti International Journal of Management Science, 2023)
This research seeks to prove the positive and significant effect of transformational leadership and empowerment on employee engagement, with job satisfaction as a mediator. The research used quantitative methods and the data was processed using SmartPLS 4. Involving 56 respondents from one of the joint venture companies in Indonesia that produces flour, the following research results were obtained: transformational leadership has a positive but not significant effect on employee engagement; empowerment has a positive and significant effect on employee engagement; transformational leadership has a positive but not significant effect on job satisfaction; empowerment has a positive and significant effect on job satisfaction; job satisfaction has a positive and significant effect on employee engagement; job satisfaction is able to mediate transformational leadership with employee engagement positively, but not significantly; job satisfaction is able to mediate empowerment with employee engagement positively, but not significantly.